A multidimensional construct of helicopter parenting and college students’ game and social media addictive behaviors: A cross-cultural study in South Korea and China - Hwang, Woosang; Fu, Xiaoyu; Kim, Seonghee; Jung, Eunjoo; Zhang, Yue (Frontiers in Psychology, 2023)
We explored latent classes of helicopter parenting among Korean and Chinese college students. In addition, we examined whether these latent classes of helicopter parenting are related to Korean and Chinese students’ game and social media addictive behaviors. A three-step latent class analysis was conducted using 452 students from six universities in South Korea and 372 students from four universities in China. We identified four distinct helicopter parenting latent classes among the parents of Korean and Chinese students: weak, strong, academic management, and academic and schedule management. We also found that Korean students in the strong class reported significantly higher levels of game and social media addictive behaviors than those in the other three classes, but this did not hold for Chinese students. This finding indicates that the association between helicopter parenting and college students’ game and social media addictive behaviors can be differentiated within Asian cultural contexts.